2016
DOI: 10.1136/injuryprev-2015-041844
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep disorders and injury: a nationwide population-based retrospective cohort study

Abstract: Comparing to patients with non-sleep disorders, patients with sleep disorders had a higher risk of injury and the risk was particularly pronounced in those who had insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…In addition, OSA among the nonobese population is treated as less adherent and ignores related treatment (Gülbay et al, 2019). Another concerning phenomenon our study found was that OSA patients aged 20-44 years had a 93% higher risk for injury than controls, inconsistent with a previous study that indicated that OSA increased with increasing age, subjects had OSA and increased the risk of injury (Lin et al, 2016). Hence, we suggest that future research should focus on a young OSA population and different types of injury.…”
Section: Individuals With Injury 2925 Individuals With Injurycontrasting
confidence: 71%
See 2 more Smart Citations
“…In addition, OSA among the nonobese population is treated as less adherent and ignores related treatment (Gülbay et al, 2019). Another concerning phenomenon our study found was that OSA patients aged 20-44 years had a 93% higher risk for injury than controls, inconsistent with a previous study that indicated that OSA increased with increasing age, subjects had OSA and increased the risk of injury (Lin et al, 2016). Hence, we suggest that future research should focus on a young OSA population and different types of injury.…”
Section: Individuals With Injury 2925 Individuals With Injurycontrasting
confidence: 71%
“…The injury event was defined by the ICD-9-CM codes (N-Code 800-999) during the period between 2000 and 2013, we further classified the injuries as unintentional (traffic, falls, and poisoning) and intentional (suicide), based on definition of injuries type by prior research (Centers for Disease Control & Prevention, 2012;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DSM-5, insomnia disorder is defined as the complaint of poor sleep occurring at least 3 nights per week for at least 3 months with associated significant daytime effects [ 4 ]. Insomnia has been associated with an increased risk of various medical [ 5 7 ] and psychiatric disorders [ 8 , 9 ] and injuries [ 10 ]. Sleep disorders in patients with medical conditions are assumed to negatively affect prognosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In DSM-5, insomnia disorder is de ned as the complaint of poor sleep occurring at least 3 nights per week for at least 3 months with associated signi cant daytime effects (4). Insomnia has been associated with an increased risk of various medical (5-7) and psychiatric disorders (8, 9) and injuries (10). Sleep disorders in patients with medical conditions are assumed to negatively affect prognosis (11).…”
Section: Introductionmentioning
confidence: 99%